PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, IKLIM SEKOLAH DAN KOMPETENSI PROFESIONAL GURU TERHADAP DISIPLIN KERJA GURU MI SWASTA DI KECAMATAN GRINGSING - Marzuki, Hadi; Nor Miyono; Rasiman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the influence of principal leadership, school climate, and teachers’ professional competence on work discipline among teachers in private Madrasah Ibtidaiyah (MI) in Gringsing District, both partially and simultaneously. Using a quantitative approach with associative methods, data were collected from 118 respondents selected through proportional random sampling from a total population of 167 teachers. Data collection was conducted using closed-ended questionnaires measured on a Likert scale, and the analysis was performed using multiple linear regression with SPSS version 26. The results showed that principal leadership significantly influenced teacher work discipline, contributing 76.2%, with fairness identified as the weakest dimension. School climate also significantly affected teacher work discipline, contributing 60.1%, although institutional environment appeared as the weakest aspect. Teachers’ professional competence demonstrated a significant influence, contributing 75.5%, with professional development identified as the weakest dimension. Simultaneously, the three variables collectively influenced teacher work discipline by 79.9%, while the remaining 20.1% was influenced by other factors outside the model. This study underscores the importance of strengthening principal leadership, fostering a conducive school climate, and enhancing teachers’ professional competence as integrated strategies to improve teacher discipline. These findings provide valuable insights for policymakers and educational leaders in developing effective strategies to enhance the quality of education in Islamic-based institutions.